Electroplating Composition for High-Hardness Silver-Bismuth Binary Alloy Coating

The electroplating composition for a silver-bismuth binary alloy addresses the issues of low hardness and instability in silver alloy plating by using potassium bismuth tartrate and other additives, achieving high hardness and gloss while being environmentally friendly.

KR103043703B1Active Publication Date: 2026-11-05설필수 +1
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
KR1020250205079
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2025-12-19
Publication Date
2026-11-05
Estimated Expiration
2045-12-19

AI Technical Summary

Technical Problem

Silver alloy plating used in electrical and electronic components faces issues with low hardness, wear resistance, and instability due to antimony precipitation, leading to reduced gloss and health and environmental concerns.

Method used

An electroplating composition forming a silver-bismuth binary alloy plating layer using potassium bismuth tartrate, Rochelle salt, selenium compound, polyphosphate, and potassium nitrate to enhance hardness and gloss without antimony, with additives like stearoxytrimethylsilane and simethicone to mitigate brittleness and surface defects.

Benefits of technology

The composition achieves high hardness (180 Hv or higher) and high gloss while being eco-friendly, with improved wear resistance and reduced brittleness, maintaining stability across varying pH and temperature conditions.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to an electroplating composition for a high-hardness silver-bismuth binary alloy film, comprising 0.1 to 10 parts by weight of a silver ion source, 0.001 to 1 part by weight of a bismuth ion source, 5 to 100 parts by weight of a tartrate, 0.0001 to 0.1 parts by weight of a selenium compound, 0.05 to 2 parts by weight of a polyphosphate, and 3 to 15 parts by weight of potassium nitrate, wherein the addition of the polyphosphate inhibits the formation of precipitates of bismuth ions, and the addition of the potassium nitrate compensates for the decrease in conductivity of the plating bath caused by the addition of the polyphosphate.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to an electroplating composition that can be applied to sockets, which are interface components for charging electric vehicles, connectors, lead frames, and printed circuit boards of electrical and electronic communication components, and can form an eco-friendly silver-bismuth binary alloy plating layer that exhibits high hardness and high gloss even without the addition of antimony. Background Technology

[0003] Silver (Ag) is widely used as a surface plating layer in a wide range of electrical and electronic component fields due to its excellent electrical conductivity, reflectivity, and corrosion resistance. However, silver has the disadvantage of having relatively low hardness and poor wear resistance, and it wears out quickly or gets scratched in environments such as electrical contacts or connectors where repetitive physical contact occurs. To solve these problems, a technology has been proposed to improve the mechanical properties of the plating layer by adding trace amounts of alloying elements to silver.

[0004] Among them, silver-antimony (Ag-Sb) alloy plating is known as a representative approach to compensate for the disadvantages of silver.

[0005] However, silver-antimony (Ag-Sb) alloy plating is Sb 3 + Due to the low chemical stability of the ions, they easily precipitate in the form of base salts or hydroxides with changes in pH or temperature fluctuations, which leads to problems such as reduced hardness and gloss.

[0006] In other words, silver-antimony (Ag-Sb) alloy plating can actually result in lower hardness due to the precipitation of metal ions and the lack of long-term stability of the plating bath, and there is a problem in that the gloss can also be reduced due to the deterioration of the brightener function and unstable surface quality caused by these precipitates.

[0007] In addition, antimony is a toxic substance used in silver-antimony alloy plating that poses a burden on workers' health and wastewater treatment.

[0008] For this reason, there is an increasing demand for alloy plating compositions that can exhibit high hardness and high gloss even without containing antimony. Prior art literature

[0010] Republic of Korea Patent Registration No. 10-953228 The problem to be solved

[0011] The present invention was devised to solve the problems described above, and aims to provide an electroplating composition that forms an eco-friendly silver-bismuth binary alloy plating layer capable of exhibiting high hardness and high gloss without the use of antimony. means of solving the problem

[0013] As a means to solve the aforementioned problems, the electroplating composition for a high-hardness silver-bismuth binary alloy film of the present invention (hereinafter referred to as the "composition of the present invention") comprises, for every 100 parts by weight of water, 0.1 to 10 parts by weight of a silver ion source, 0.001 to 1 part by weight of a bismuth ion source, 5 to 100 parts by weight of a tartrate, 0.0001 to 0.1 parts by weight of a selenium compound, 0.05 to 2 parts by weight of a polyphosphate, and 3 to 15 parts by weight of potassium nitrate, wherein the addition of the polyphosphate suppresses the formation of precipitates of bismuth ions, and the addition of the potassium nitrate compensates for the decrease in conductivity of the plating bath caused by the addition of the polyphosphate.

[0014] As one example, the above bismuth ion source is characterized as being potassium bismuth tartrate.

[0015] As one example, the above tartrate is characterized as being a Rochelle salt.

[0016] As an example, it is characterized by further including 0.0005 to 0.1 parts by weight of stearoxytrimethylsilane.

[0017] delete

[0018] delete

[0019] As an example, it is characterized by further including 0.0005 to 0.02 parts by weight of simethicone. Effects of the invention

[0021] As explained above, the composition of the present invention has the advantage of enabling high hardness (180 Hv or higher) by controlling the formation of insoluble precipitates while enabling high gloss.

[0022] In addition, the present invention has the advantage of being eco-friendly by allowing less harmful bismuth to be applied without the use of antimony.

[0023] In addition, the composition of the present invention has the advantage of improving wear resistance by enhancing resistance to brittleness. Specific details for implementing the invention

[0025] Hereinafter, the structure and operation of the present invention will be explained in more detail with reference to the attached drawings. In describing the present invention, terms and words used in this specification and claims must be interpreted in a meaning and concept consistent with the technical spirit of the present invention, based on the principle that the inventor can appropriately define the concept of the terms to describe his invention in the best way possible.

[0027] The composition of the present invention is characterized by comprising, per 100 parts by weight of water, 0.1 to 10 parts by weight of a silver ion source, 0.001 to 1 part by weight of a bismuth ion source, 5 to 100 parts by weight of a tartrate, and 0.0001 to 0.1 parts by weight of a selenium compound.

[0028] The above silver ion source (Ag + As a main metal source for forming a plating layer, silver nitrate (AgNO3), silver sulfate, silver amino complex, etc., which have excellent solubility and dissociability, can be applied.

[0029] Silver nitrate has the advantage of high solubility in aqueous solution, excellent dissociability of silver ions, and forming stable complexes with Rochelle salt and tartrate salts described below, which can uniformly supply silver ions during the plating process.

[0030] The above bismuth ion source (Bi 3+ The method involves selectively adsorbing fine Bi-microparticles onto the silver surface or inducing a reduction in surface roughness (Ra), crystal refinement, and uniformization of inter-crystal gaps, thereby significantly improving the glossiness of the plating layer.

[0031] The above bismuth ion sources may include bismuth nitrate, bismuth chloride, bismuth sulfate, bismuth citrate, bismuth tartrate, etc.

[0032] Among these, the bismuth tartrate series is mediated by tartrate ligands Bi 3 + Since the ions are stably chelated, there is an advantage of effectively suppressing hydrolysis and precipitation in the plating bath.

[0033] In particular, potassium bismuth tartrate has the best solubility in aqueous solution and complex stability among tartrate-based bismuth compounds, making it most suitable for long-term stability of electroplating baths and uniform deposition.

[0034] The above tartrate forms a stable complex in solution through a complexation reaction with silver and bismuth ions, thereby controlling the precipitation of metal ions and the formation of base salts. Potassium sodium tartrate (Rochelle salt), potassium tartrate, sodium tartrate, etc. may be used as the above tartrate.

[0035] In particular, sodium potassium tartrate (Rochelle salt) is the most desirable among the above tartrate salts because it has excellent solubility, buffering capacity, and complexing ability, thereby most effectively achieving the stabilization of metal ions in the electroplating bath.

[0036] Silver and bismuth ions tend to precipitate in aqueous solutions in the form of hydroxides or base salts, but Rochelle salt forms appropriate complexes with these metal ions to inhibit precipitation and stabilize the plating bath. In addition, Rochelle salt contributes to the crystallization of the plating layer by gently controlling the supply rate of silver ions during plating, and also performs the function of assisting the action of the brightener.

[0037] The above selenium-based compound acts as a brightener, refining silver crystal grains and improving surface leveling through surface-selective adsorption. It exhibits a powerful gloss / smoothing effect even in minute amounts.

[0038] Meanwhile, silver-bismuth plating has the advantage of very high hardness, but consequently, the brittleness of the plating layer increases, which may cause microcracks and delamination during bending deformation.

[0039] Accordingly, the present invention provides an example in which, in addition to the above compositions, 0.001 to 0.02 parts by weight of stearoxytrimethylsilane are further included.

[0040] The above-mentioned stearoxytrimethylsilane is an organic additive having a long stearyl chain and a silane structure, which selectively adsorbs to the intergranular region of silver crystals during the plating process to relieve local stress and reduce the brittleness of the plating layer.

[0041] These stearoxytrimethylsilanes alleviate brittleness problems, improving bending durability while maintaining the hardness of the plating layer (180 Hv or higher).

[0042] Meanwhile, as previously mentioned, Rochelle salt is added to the composition of the present invention to control the formation of precipitates. However, in order to further increase the efficiency of controlling the formation of such precipitates and to double the hardness and glossiness, the present invention provides an example in which, in addition to the above compositions, 0.05 to 2 parts by weight of polyphosphate are further included per 100 parts by weight of water.

[0043] Bi 3 + It is sensitive to changes in pH and precipitation occurs easily, but polyphosphates form weak complexes with these metal ions to increase stability in solution.

[0044] The above polyphosphate may include sodium pyrophosphate, sodium triphosphate, sodium hexametaphosphate, sodium polyphosphate, etc.

[0045] On the other hand, while the addition of only polyphosphate is advantageous for stabilizing metal ions, it can act as a factor that reduces the conductivity of the plating solution and lowers gloss. If the conductivity of the plating bath decreases, the migration speed of metal ions slows down, leading to irregular electrodeposition rates and grain coarsening, which causes a decrease in hardness. Furthermore, since reduced conductivity inhibits the selective adsorption of brighteners and weakens the surface leveling effect, it can cause a decrease in the gloss of the plating layer.

[0046] Accordingly, the present invention provides an example in which 3 to 15 parts by weight of potassium nitrate are further included in addition to the polyphosphate.

[0047] The above potassium nitrate has the function of increasing the conductivity of the plating bath and improving the electrodeposition rate without strongly complexing with metal ions. Due to this, the hardness and gloss of the plating layer can be doubled.

[0048] On the other hand, when potassium nitrate is added, the increase in conductivity and the influence of gas generation reactions can lead to an increase in bubbles in the plating bath, which can cause pinholes and pitting on the surface of the plating layer and result in a decrease in gloss.

[0049] Accordingly, the present invention provides an example in which 0.001 to 0.01 parts by weight of simethicone are further included in addition to the above composition.

[0050] The above simethicone is a siloxane-based defoaming agent that suppresses the generation of bubbles and adhesion to the plated surface during plating, thereby minimizing surface defects that may occur during the formation of the plating layer and enabling the expression of effects that improve gloss and surface uniformity.

[0052] Embodiments of the present invention are explained below through experimental examples.

[0053] As shown below, after preparing each plating solution, a degreasing and activated brass plate (thickness 0.5 mm, 20 mm × 50 mm) was used as the cathode, the temperature was 25℃, and the current density was 1.0 A / dm². 2 , plating was performed under conditions of a plating time of 10 minutes to form a plating layer approximately 10 μm thick. After plating, the specimens were washed with pure water and dried at 60°C for 10 minutes, after which the following brittleness evaluation, hardness measurement, and gloss measurement tests were performed, and the results are shown in Table 1.

[0054] First, for the brittleness evaluation, each plated specimen was cut to a width of 10 mm to prepare a test specimen. Then, using a mandrel with a diameter of 5 mm, a 180° bend was defined as one cycle with the plating layer facing outward, and repeated bending was performed. After each bend, the outer side of the bent portion was observed under an optical microscope (magnification 200x), and the point at which a noticeable crack or delamination was first observed in the plating layer was recorded as the "number of times the first crack occurred."

[0055] Next, a micro Vickers hardness tester was used for hardness measurement. The test load was set to 25 gf (0.245 N) and the holding time was set to 10 seconds. For each specimen, hardness values ​​were measured at five different points, and the average value was taken as the hardness value.

[0056] Next, gloss was measured using a gloss meter under a 60° angle of incidence condition. Gloss was measured at five points relative to the center of the plated surface of each specimen, and the average value was taken as the gloss. The unit used was 60° Gloss Unit (GU).

[0058] <Example 1>

[0059] A plating solution was prepared to contain 2 parts by weight of a silver ion source (silver nitrate), 0.03 parts by weight of a bismuth ion source (potassium bismuth tartrate), 25 parts by weight of Rochelle salt, and 0.003 parts by weight of a selenium compound (selenate) per 100 parts by weight of water.

[0061] <Example 2>

[0062] A plating solution was prepared in the same manner as in Example 1, but with an additional 0.002 parts by weight of stearoxytrimethylsilane.

[0064] <Example 3>

[0065] A plating solution was prepared in the same manner as in Example 1, but with an additional 0.15 parts by weight of polyphosphate (sodium pyrophosphate).

[0067] <Example 4>

[0068] A plating solution was prepared in the same manner as in Example 3, but with an additional 8 parts by weight of potassium nitrate.

[0070] <Example 5>

[0071] A plating solution was prepared in the same manner as in Example 4, but with an additional 0.005 parts by weight of simethicone.

[0073] division Number of bends at which the first crack occurs (times) Vickers hardness Hv (average, n=5) 60° Glossiness (GU, average, n=5) Example 1 8 180 88 Example 2 18 179 89 Example 3 10 183 91 Example 4 9 186 93 Example 5 12 186 96

[0075] When comparing Example 1 and Example 2 in terms of brittleness, in the case of Example 2, the number of bending cycles at which the first crack occurs was significantly increased compared to Example 1 due to the addition of more stearoxytrimethylsilane, confirming the effect of mitigating the brittleness of the plating layer.

[0076] In addition, in Examples 4 and 5, it can be seen that the bending durability is somewhat improved compared to Example 1 due to the addition of polyphosphate and potassium nitrate, and in particular, in the case of Example 5 which further contains simethicone, it can be seen that cracks occur at a higher number of bending cycles than in Examples 3 and 4, which is attributed to the reduction of local brittle defects caused by bubbles.

[0077] Next, we examine the hardness and gloss. In terms of hardness, it was confirmed that in almost all embodiments, a high-hardness plating layer was formed with a Vickers hardness of 180 Hv or higher.

[0078] In Example 3, it can be seen that the density of the plating layer is improved by suppressing the formation of precipitates in the plating bath through the addition of polyphosphate, and as a result, compared to Example 1, the hardness increased from 180 Hv to 183 Hv and the glossiness increased from 88 GU to 91 GU.

[0079] In addition, in Example 4, potassium nitrate was added in addition to the polyphosphate to compensate for the conductivity that could be reduced by the polyphosphate, thereby improving the electrodeposition efficiency. As a result, the hardness was further increased to 186 Hv, and the gloss was also improved to 95 GU.

[0080] In addition, in Example 5, simethicone was further included to suppress bubble formation that may increase incidentally due to the addition of potassium nitrate, and as a result, pinhole and pitting defects on the surface of the plating layer were reduced, showing the highest gloss value of 96GU.

[0081] Meanwhile, as it can be seen that in Example 2, in which stearoxytrimethylsilane was added, substantially equivalent hardness and glossiness were maintained compared to Example 1, it can be seen that brittleness can be mitigated without a decrease in hardness and glossiness by adding stearoxytrimethylsilane.

[0083] From the above description, those skilled in the art will understand that various changes and modifications are possible within the scope of the technical concept of the present invention. Accordingly, the technical scope of the present invention should not be limited to the contents described in the detailed description of the specification, but should be determined by the claims.

Claims

Claim 1 An electroplating composition for a high-hardness silver-bismuth binary alloy film, comprising 0.1 to 10 parts by weight of a silver ion source, 0.001 to 1 part by weight of a bismuth ion source, 5 to 100 parts by weight of a tartrate, 0.0001 to 0.1 parts by weight of a selenium compound, 0.05 to 2 parts by weight of a polyphosphate, and 3 to 15 parts by weight of potassium nitrate, wherein the addition of the polyphosphate inhibits the formation of precipitates of bismuth ions, and the addition of the potassium nitrate compensates for the decrease in conductivity of the plating bath caused by the addition of the polyphosphate. Claim 2 An electroplating composition for a high-hardness silver-bismuth binary alloy film, characterized in that, in claim 1, the bismuth ion source is potassium bismuth tartrate. Claim 3 An electroplating composition for a high-hardness silver-bismuth binary alloy film according to claim 1, characterized in that the tartrate is a Rochelle salt. Claim 4 An electroplating composition for a high-hardness silver-bismuth binary alloy film, characterized in that, in claim 1, it further comprises 0.001 to 0.02 parts by weight of stearoxytrimethylsilane. Claim 5 delete Claim 6 delete Claim 7 An electroplating composition for a high-hardness silver-bismuth binary alloy film, characterized in that, in claim 1, it further comprises 0.001 to 0.01 parts by weight of simethicone.

Citation Information

Patent Citations

  • Sedimentation improving agent for material to be plated, and barrel plating method using the sedimentation promoting agent

    JP2008266714A

  • Cyanide-free electrolyte for silver deposition

    JP2021535276A

  • Method for manufacturing color steel sheets

    KR1020130026150A

  • Low temperature bonding method using metal coating layer with exothermic and amorphous characteristics

    KR1020170014720A

  • Silver-Bismuth Electrolyte for Separating Hard Silver Layers

    US20240035184A1